Penerapan Program Pengabdian Kepada Masyarakat Berdasarkan Pendidikan Berkualitas Untuk Anak Usia Prasekolah, Taman Kanak-Kanak, Dan Sekolah Dasar di Desa Tambah Rejo Barat, Dusun 1 - Annajim Daskar; Siffa Salsabilla; Elisya Elisya; Mamay Mamay; Wasilatun Marfuah; Adhistya Putri Valentine; Yulan Putri Pratiwi; Nana Maulida; Adila Pangestu; Jitu Adillah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The Akhlakul Karimah Community Service Program (KKN) with Impact is an intracurricular program that combines the dharma of education, research, and community service..This program aims to provide space for students to actualize academic competencies to solve real problems in villages by prioritizing moral and ethical values..The implementation of KKN in [Mention Village Name] is carried out for one month with a focus on interdisciplinary programs that are aligned with the SDGs theme, such as [Mention Theme, for example: health, creative economy, or digital literacy].The implementation method includes stages of observing social situations, coordinating with village stakeholders , training, and implementing appropriate technology (TTG)..The results of the activity show an increase in [State the achievement, for example: health literacy or economic independence of MSMEs] and strengthening of student character through the implementation of noble moral values..The outputs of this activity include a final report, community service journal articles, video documentation, and posters of the activity results.